Comparison of Two Main Orthokeratology Lens Designs in Efficacy and Safety for Myopia Control - Lu, Weiwei; Ning, Rui; Diao, Kai; Ding, Yang; Chen, Ruru; Zhou, Lei; Lian, Yan; McAlinden, Colm; Sanders, Francis W. B.; Xia, Fangfang; Huang, Jinhai; Jin, Wanqing (Frontiers in Medicine, 2022)
Purpose: To compare efficacy and safety of CRT (Corneal Refractive Therapy) lenses and VST (Vision Shaping Treatment) lenses for myopia control in children. Methods: Medical records of 1001 children (2002 eyes) who had been fitted with orthokeratology lenses for over 1.5 years were retrospectively reviewed. We collected the clinical data of four types of OK (Orthokeratology) lenses available: one CRT lens (brand: CRT) and three VST lenses (brands: Euclid, Alpha and Hiline) over 1.5 years. Results were compared and analyzed with a one-way ANOVA and Pearson’s chi-square test. Results: Axial length elongation in the CRT lens group was 0.13±0.02mm faster than that in the Euclid lens, 0.10±0.02mm faster in the Alpha lens, and 0.08±0.02mm faster in the Hiline lens over the 1.5-year period (all P<0.05). 37.3% of subjects using the CRT lens experienced more than 1.00 D of refractive growth, compared with 20.2% to 30.8% of subjects wearing the three groups VST lenses (all P<0.05). A lower incidence of total adverse events was found with the CRT lenses compared with the VST lenses (P<0.05), especially corneal staining. No difference was found in axial length elongation, refraction growth and incidence of adverse events among the three types of VST lenses (all P>0.05). Conclusions: Compared with the VST lenses, CRT lenses demonstrated a weaker effect on myopia control but with a better safety profile. Different types of VST lenses had similar efficacy and safety in the context of controlling myopia progression.